Cobalt Oxide and Cobalt‐Graphitic Carbon Core–Shell Based Catalysts with Remarkably High Oxygen Reduction Reaction Activity. Issue 9 (23rd April 2016) - Yu, Jie; Chen, Gao; Sunarso, Jaka; Zhu, Yinlong; Ran, Ran; Zhu, Zhonghua; Zhou, Wei; Shao, Zongping
Abstract : The vital role of ethylenediaminetetraacetic acid on the structure and the oxygen reduction reaction activity of the non‐precious‐metal‐based pyrolyzed catalyst is reported and elaborated. The resultant catalyst can overtake the performance of commercial Pt/C catalyst in an alkaline medium.